Prinsip-Prinsip dan Strategi Dakwah Islamiyah dalam Konteks Kontemporer - Aceng Badruzzaman; Ermanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article examines Islamic da'wah's principles and strategies in a contemporary context, with a focus on the relevance and adaptability of da'wah methods to modern-day challenges. In the era of rapid globalization and information technology, Islamic da'wah requires an innovative and contextual approach to achieve optimal effectiveness. This research uses a qualitative approach with literature analysis and case studies of several successful da'wah movements. The research results show that the basic principles of da'wah, such as sincerity, patience, and wisdom, remain the main foundation. However, da'wah strategies need to be adapted to utilize digital technology, social media, and interreligious dialogue. In addition, research has shown that inclusive da'wah, focused on socio-economic solutions for society, effectively engages people and encourages their participation. Thus, this article makes an important contribution to enriching the Islamic da'wah literature and offers practical guidance for preachers in conveying the Islamic message more effectively in the contemporary era.